Development of ispring suite 9 learning media to improve learning outcomes - Yuhandani, Syadira Rahma; Putra, Galih Mahardika Christian (Universitas Jambi, Indonesia, 2025)
This research was development research (R&D) with the ADDIE model that aimed to design and develop learning media using iSpring Suite 9 for grade IV elementary school students, especially in science and social studies. In addition, this research also aims to test the feasibility and effectiveness of the developed media. This research used test and non-test techniques, which included observation, interviews, questionnaires, and documentation. The validity test results showed that Keratara learning media obtained a score of 92% from media experts based on appearance, usage, and usefulness. Meanwhile, the material validation, which included aspects of accuracy with the material, suitability for the thinking ability of students, support for learning content, and achievement of learning objectives, received a score of 95%. Therefore, the findings indicated that the iSpring Suite 9-based interactive learning media developed is valid and effective in supporting elementary school students’ learning process and improving their learning outcomes.